Corecovery of Bio-Oil and Fermentable Sugars from Oil-Bearing Biomass - Godwin Severa; Guneet Kumar; Michael J. Cooney (International Journal of Chemical Engineering)
The applicability of ionic liquid-methanol cosolvent system to both extract bio-oil and simultaneously pretreat the carbohydrate fraction of jatropha and safflower biomass for enzymatic hydrolysis to fermentable sugars is presented. Although pretreatment with either the cosolvent or pure ionic liquid yielded comparable hydrolysis kinetics and fermentable sugar yields on safflower whole seeds, the addition of alcohol to the ionic liquid was necessary to optimally recover both bio-oil and fermentable sugars. The ionic liquid [C2mim][Ac] was far more effective than [C2mim][MeSO4] with optimum processing conditions occurring at a cosolvent concentration of 70–30 wt% of [C2mim][Ac] to methanol and a processing temperature of 120°C. Under these conditions, the majority of the bio-oil was extracted and 25.4 wt% (safflower) and 14.3 wt% (jatropha) of the whole seed biomass were recovered as fermentable sugars. The recovery of fermentable sugars from the carbohydrate fraction was as high as 74% and 78% for jatropha and safflower seeds, respectively, when using [C2mim][Ac] cosolvent. A preliminary theoretical analysis of two potential oil seed processing pathways using the cosolvent system suggested that the corecovery of bio-oil, fermentable sugars, and a protein rich meal can recover a majority of the energy contained in the original biomass—a result that improves upon the traditional approach of solely extracting bio-oil.